Film discourse: the semantic interpretation of film titles - Kurkimbayeva, A.M. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
This article discusses the problems of semantic interpretation of the titles of feature films, as films turned into influential means of mass communication in the modern life. Filmonyms as one of the types of small-format texts has become the object of linguistic research. The significance of the film discourse as an audiovisual discourse is determined by the possibilities of its impact on the addressee. Author comprehensively analyzed the works of foreign and Kazakhstani linguists who studied the film discourse from various aspects. The purpose of the article is to identify linguistic and pragmalinguistic interpretation of Kazakhstani film titles. To achieve the goal, the following tasks were set: to consider semantic interpretation of the titles of feature films, to identify aesthetic function of film discourse, to group films into semantic categories, to offer the definition of the concept of “film discourse”. The scientific significance of the research work expands the research scope of film-discourse as a type of institutional discourse. Practical significance is due to the fact that research results can be used as materials for preparing lectures and cases on audiovisual discourse and pragmalinguistic features applied to the names of Kazakhstani films should undoubtedly become the object of further research by linguists.
Кинодискурс: кино атауларының семантикалық интерпретациясы
Кинодискурс: семантическая интерпретация названий фильмов
Keywords: film discourse; film titles; filmonyms; semantics; interpretation; addressee; communicative impact; verbal communication